Direct patterning of polystyrene–polymethyl methacrylate copolymer by means of laser interference lithography using UV laser irradiation - Lasagni, A.F. (2008)
The fabrication of functionalized surfaces on polymericsubstrates is of importance in chemistry, biology,physics, and material science. Examples of functionalsurfaces are micro/nano periodic arrays that can befabricated using different methods. However, many ofthese techniques require several fabrication steps. Inthis communication, we report the fabrication of advancedarchitectures in poly(methylmethacrylate)?polystyrene(PMMA?PS) copolymers using direct laserinterference patterning. Because of the mixed opticalproperties of the copolymers, a different type of periodicarchitectures could be fabricated when comparedwith traditional pure polymers. This new type of periodicstructures results from the local swelling of thecopolymer due to the formation of gaseous productsinduced by the laser radiation. Additionally, relativelylow laser fluences are necessary to initiate the ablationprocess of the copolymers.